Hematoporphyrin encapsulated polymeric nanomicelles - Barati, Amir Houshang; Hejazi, Peyman; Hasanzadeh, Hadi (Archives of Advances in Biosciences, 2012)
Nowadays, developements in nanotechnology have leeds an increased application of this newborn technology in cancer treatment. In this study, a stabilized micelle was developed to load HpD in order to be used in photodynamic treatment of cancer in an animal model. To construct micelles, Pluronic P-105 was used and stabilized to encapsulate HpD. This process includes a 24 h polymerization in which the first 3.5 h was in the presence of N2 purge and was continued at 65°C. In this reaction, NNDEA and benzoil peroxide (BP) were used for stabilization of micelles and initiation of reaction, respectively. DLS analysis of micelles revealed that the size of them before and after drug encapsulation was 14 nm and 23.5 nm, respectively. To assess drug loading, drug standard curve was obtained and its loading was obtained as 2 mg/ml. To extract free drug from complex, it was dialyzed against water and its stability profile was measured up to one month which was more than 80%. According to obtained results, this complex could be used to reduce side effects in photodynamic therapy. Besides, according to tumor characteristics and physical properties of micelles, it is possible to enhance drug release and uptake at tumor site.